PERUBAHAN KOMPONEN KIMIA BUAH MAKADAMIA (MACADAMIA HILDEBRANDII STEEN) SELAMA PENYIMPANAN - Abdul Hakim Lukman; Toga Silitonga (Jurnal Penelitian Hasil Hutan, 1989)
This  work  investigates   the  use of  macadamia  (Macadamia hildebrandii   Steen)  fruit.   The samples  were obtained  from Forest  District  of  Simalungun,   North  Sumatera  province  of Indonesia.  The nut samples  were allowed  to stand  for a period of  zero   week  as control,   the  others  were  kept  for  4 and  8  weeks.   The  macadamia   kernels  were also stored  for  4 and  8 weeks.  The  analyses  comprised   of  the  determination    of  moisture.    ash,   fat  and protein   contents.The  study   reveals  that  the  moisture   content   varies from   17. 7 -   24.6   percent,   ash  from  2. 7 -  2.9 percent,  fat from0.9  -   2.0  percent,   and  protein   from  6.3  -   8.4  percent.    Themoisture,    fat, and protein   contents   were  effected  by  fruit condition  and  storage  time,   while ash contents   not  influenced.   The  macadamia  kernels   stored  for  8 weeks  have smaller moisture   content.   Fat  content   of  macadamia  nuts  decreased   at stored   for  4 and 8 weeks,and protein  content   of macada-mia nuts  and kernels  decreased  at stored  for